2019
DOI: 10.1111/2041-210x.13327
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotope analysis to answer fundamental questions in invasion ecology: Progress and prospects

Abstract: 1. What makes some species successful invaders while others fail, and why some invaders have major impacts in invaded ecosystems are pivotal questions that are attracting major research effort. The increasing availability of high resolution, georeferenced stable isotope landscapes ('isoscapes'), coupled with the commercialization of stable isotope-enriched tracer molecules and the development of new analytical approaches, is facilitating novel applications of stable isotope techniques in ecology.We can now add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 240 publications
(234 reference statements)
1
32
0
Order By: Relevance
“…Recently, SIA has been highlighted in a few studies addressing fundamental issues in invasion ecology (Kamenova et al, 2017), especially in answering questions relating to the ecological mechanisms underlying invasion processes, such as invasion pathway, and the impacts of invasive species (Mccue et al, 2020). For example, Vander Zanden et al (1999 demonstrated that the diet of the native lake trout (Salvelinus namaycush) was shifted from littoral to pelagic habitat with reduced trophic position following the invasion of exotic smallmouth bass Micropterus dolomieu and rock bass Ambloplites rupestris in North American boreal lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SIA has been highlighted in a few studies addressing fundamental issues in invasion ecology (Kamenova et al, 2017), especially in answering questions relating to the ecological mechanisms underlying invasion processes, such as invasion pathway, and the impacts of invasive species (Mccue et al, 2020). For example, Vander Zanden et al (1999 demonstrated that the diet of the native lake trout (Salvelinus namaycush) was shifted from littoral to pelagic habitat with reduced trophic position following the invasion of exotic smallmouth bass Micropterus dolomieu and rock bass Ambloplites rupestris in North American boreal lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Our extensive isotopic analyses of the feathers of adult and juvenile starlings collected in winter at dairies and feedlots across the U.S. revealed considerable isotopic variability associated with movements among states. These results underline the utility of the isotope approach to investigate movement patterns of such introduced species, especially within context of management approaches [ 18 ]. We predicted that starlings collected south of 40° latitude would primarily be assigned to the collection state because starling populations south of 40° latitude exhibited little migration in winter away from their nesting location [ 22 ].…”
Section: Discussionmentioning
confidence: 90%
“…Describing movements of abundant species across state boundaries, where control measures may vary, has hitherto been virtually impossible based on conventional tracking technologies [ 16 ]. The measurement of intrinsic markers, such as abundance of naturally-occurring stable isotopes, has emerged as an effective tool in assigning migratory birds to their molt origin [ 17 ] in particular and in investigating fundamental questions regarding invasion ecology [ 18 ], in general.…”
Section: Introductionmentioning
confidence: 99%
“…Islands are a unique and relatively harsh environment for cottonmouth snakes, which are most often associated with freshwater habitats (Gloyd & Conant, 1990). Ecological characteristics that are predicted to predispose a species to successful invasion of novel habitats often include flexibility of feeding strategies and dietary breadth (Ehrlich, 1989; Vasquez, 2005; Blackburn et al ., 2009; Lillywhite & Martins, 2019; McCue et al ., 2020). Similarly, insular populations surviving on subsidies are thought to require a wide trophic niche (Ruffino et al ., 2011) in order to persist when the abundance and availability of food subsidies changes (Stapp & Polis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stable isotope values of nitrogen (i.e., δ 15 N) increase with increasing trophic position and can therefore be used to determine the trophic level at which an animal is feeding (e.g., Vander Zanden et al ., 1998; Vanderklift & Ponsard, 2003; Schwamborn & Giarrizzo, 2014). Standardized metrics for quantifying the trophic niche of individuals using δ 13 C and δ 15 N values can be used to make comparisons between groups or changes through time and space (Layman et al ., 2007; Jackson et al ., 2011; McCue et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%